2013
DOI: 10.1371/journal.pone.0082459
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Acylcarnitines Are Altered in Prediabetic Conditions

Abstract: ObjectiveThe role of mitochondrial function in the complex pathogenesis of type 2 diabetes is not yet completely understood. Therefore, the aim of this study was to investigate serum concentrations of short-, medium- and long-chain acylcarnitines as markers of mitochondrial function in volunteers with normal, impaired or diabetic glucose control.MethodsBased on a 75 g oral glucose tolerance test, 1019 studied subjects were divided into a group with normal glucose tolerance (NGT; n = 636), isolated impaired fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
162
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 30 publications
15
162
1
Order By: Relevance
“…Similarly, Satish C. Kalhan et al discovered that 14 carnitines in serum increased in NAFLD [6]. A study on serum levels of acylcarnitines showed that a lot of carnitines were higher in T2DM, especially tetradecenoylcarnitine and tetradecadienylcarnitine [15]. What's more, we discovered that serum tetradecenoylcarnitine and tetradecadienylcarnitine were higher in NAFLD + T2DM compared with NAFLD.…”
Section: Differential Metabolites From Both Populationssupporting
confidence: 58%
“…Similarly, Satish C. Kalhan et al discovered that 14 carnitines in serum increased in NAFLD [6]. A study on serum levels of acylcarnitines showed that a lot of carnitines were higher in T2DM, especially tetradecenoylcarnitine and tetradecadienylcarnitine [15]. What's more, we discovered that serum tetradecenoylcarnitine and tetradecadienylcarnitine were higher in NAFLD + T2DM compared with NAFLD.…”
Section: Differential Metabolites From Both Populationssupporting
confidence: 58%
“…Moreover, significantly different acylcarnitine profiles were observed among subjects with normal glucose tolerance, prediabetic states, or type 2 diabetes in a German study (22). Recently, several prospective studies indicated that medium-and/or long-chain acylcarnitines predicted cardiovascular events or mortality in people aged .85 years or selected patients undergoing cardiac catheterization or dialysis (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Although typically short‐lived, LCAC accumulate in states of inefficient fatty acid oxidation (FAO), which may be attributed to (1) defects in mitochondrial FAO enzymes or (2) increased FAO relative to tricarboxylic acid (TCA) flux; this leads to a bottleneck of carbon substrates at the TCA cycle 53, 54. Such defects can be caused or exacerbated by IR, which has, in turn, been associated with elevations in plasma LCAC 54, 55, 56, 57. However, we found no correlation between plasma LCAC and IR in this study; this suggests that the observed LCAC elevations were not driven by IR 54, 55, 56, 57.…”
Section: Discussionmentioning
confidence: 99%
“…Such defects can be caused or exacerbated by IR, which has, in turn, been associated with elevations in plasma LCAC 54, 55, 56, 57. However, we found no correlation between plasma LCAC and IR in this study; this suggests that the observed LCAC elevations were not driven by IR 54, 55, 56, 57. Regardless of the precise cause, LCAC are transported out to the plasma, where they are subsequently metabolized in several tissues (especially skeletal muscle, liver, and heart) or excreted in urine or bile 52, 56, 57.…”
Section: Discussionmentioning
confidence: 99%